(untitled) (Global Journal of Management and Business Research, 2023)
In Bangladesh growing environmental consciousness has caused a substantial shift in the green product market during the past few years. Today’s consumers are "thinking green" and are prepared to pay more for ecologically friendly goods. Impulse buying is one of the many diverse purchasing habits that consumers have. Impulse purchase or buy is any unplanned purchase made by a consumer. The research aims to discover and analyze the elements that influence consumers’ impulsive purchases of green beauty products. The researched constructs were adjusted and confirmed by exploratory and confirmatory factor analyses. With the help of the statistical program Smart PLS 2.0, the study’s paradigm was applied to the perspectives of 214 respondents in the city of Dhaka. According to the study’s findings, perceived product benefits, environmental concerns, sales promotion, and peer pressure are all significantly positively associated with impulsive purchase behavior. Surprisingly, however, the notion of green trust and packaging has shown adverse effects. The study’s result also assists past research studies in this field by validating the findings. The study will also aid green cosmetics marketers in creating successful marketing strategies by enabling them to understand better regarding many factors influencing consumers’ perceptions and impulsive purchasing behavior.